2015
DOI: 10.1039/c4gc01990c
|View full text |Cite
|
Sign up to set email alerts
|

Simple metal salts supported on montmorillonite as recyclable catalysts for intramolecular hydroalkoxylation of double bonds in conventional and VOC-exempt solvents

Abstract: We describe herein an efficient and particularly sustainable catalytic system for the intramolecular hydroalkoxylation of double bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…We screened a series of Lewis and Brønsted acids in a test reaction with citral and orcinol (5‐methylresorcinol), thereby focusing on the second step. The acids screened included Lewis acids such as ZnBr 2 , Ti(O i Pr) 4 , and TiCl 4 ; solid catalysts such as Amberlyst and zeolite; and montmorillonite‐doped with metal cations (M‐MMT), a type of solid catalyst that we recently used as a Lewis acid in C–O and C–C bond‐forming processes . The most interesting results are summarized in Table (see Supporting Information for additional examples).…”
Section: Resultsmentioning
confidence: 99%
“…We screened a series of Lewis and Brønsted acids in a test reaction with citral and orcinol (5‐methylresorcinol), thereby focusing on the second step. The acids screened included Lewis acids such as ZnBr 2 , Ti(O i Pr) 4 , and TiCl 4 ; solid catalysts such as Amberlyst and zeolite; and montmorillonite‐doped with metal cations (M‐MMT), a type of solid catalyst that we recently used as a Lewis acid in C–O and C–C bond‐forming processes . The most interesting results are summarized in Table (see Supporting Information for additional examples).…”
Section: Resultsmentioning
confidence: 99%
“…Many of these materials, however, suffer from challenges around high toxicity or high cost. There has therefore been interest in the application of iron salts to overcome these challenges. The first studies on heterogeneous iron catalysts were presented in 2015 by Antoniotti et al These employed montmorillonite-supported iron, achieving yields of up to 86% for the hydroalkoxylation of 5-methyl-2,2-diphenyl-4-hexen-1-ol to 2,2-dimethyl-5,5-diphenyltetrahydro-2H-pyran in dimethyl carbonate (DMC) as a solvent. The further development of low-cost, active, heterogeneous catalysts based on earth-abundant materials remains a desirable objective.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Iron (III) chloride can also be supported on montmorillonite as natural inorganic material to provide a very effective heterogeneous and reusable catalyst for this process. In 2015, the supported Fe-MMT catalyst developed by Antoniotti et al showed good activity and selectivity at 80 • C in dimethyl carbonate (DMC) for the cyclization of alkenols with various substitution patterns on the alkene moiety (Figure 2) [49,50]. This heterogeneous catalyst, which can be reused several times without loss of activity, displays higher activity and selectivity than those of reactions carried out under homogeneous catalysis.…”
Section: Hydroalkoxylationmentioning
confidence: 99%